Expression of the proinflammatory marker CD34 in varicose leg veins - Sushkou, S. A.; Samsonava, I.V.; Galishevich, M. M. (Phlebologie, 2015)
Objective: To study the CD34 expression in the leg veins with primary varicose veins.Material and Methods: The study included 18 patients with lower limbs varicose veins and deep vein valves insufficiency of C3 and C4 clinical classes (CEAP). To correct blood flow phlebectomy was accompanied by posterior tibial veins resection. Using immunohistochemistry, we compared the expression of CD34 in resected posterior tibial veins specimens and vena saphena magna distal fragment.Results: Posterior tibial veins wall in patients with lower limb varicosity and deep veins valves insufficiency vary the CD34 degree expression comparing with the control group. Total area of expression was significantly greater than in control sample. CD34 expression area was also significantly greater in vena saphena magna than in control group. CD34 expression comparison in the specimens from patients with varicose veins showed its significantly higher degree in the vena saphena magna than in tibial veins.Conclusion: With primary varicose veins superficial and deep leg veins develop unidirectional increase of CD34 expression, that can be assumed as a pathogenetic factors of further disease progression and involvement of deep vein valves.
Keywords: Primary varicose veins; vein wall; CD34 expression